Encroachment drives facilitation at alpine shrublines - Yafeng Wang; Eryuan Liang; J. Julio Camarero (Forest Ecosystems, 2024)
Ongoing encroachment is driving recent alpine shrubline dynamics globally, but the role of shrub-shrub interactions in shaping shrublines and their relationships with stem density changes remain poorly understood. Here, the size and age of shrubs from 26 Salix shrubline populations along a 900-km latitudinal gradient (30°–38° N) were measured and mapped across the eastern Tibetan Plateau. Point pattern analyses were used to quantify the spatial distribution patterns of juveniles and adults, and to assess spatial associations between them. Mean intensity of univariate and bivariate spatial patterns was related to biotic and abiotic variables. Bivariate mark correlation functions with a quantitative mark (shrub height, basal stem diameter, crown width) were also employed to investigate the spatial relationships between shrub traits of juveniles and adults. Structural equation models were used to explore the relationships among conspecific interactions, patterns, shrub traits and recruitment dynamics under climate change. Most shrublines showed clustered patterns, suggesting the existence of conspecific facilitation. Clustered patterns of juveniles and conspecific interactions (potentially facilitation) tended to intensify with increasing soil moisture stress. Summer warming before 2010 triggered positive effects on population interactions and spatial patterns via increased shrub recruitment. However, summer warming after 2010 triggered negative effects on interactions through reduced shrub recruitment. Therefore, shrub recruitment shifts under rapid climate change could impact spatial patterns, alter conspecific interactions and modify the direction and degree of shrublines responses to climate. These changes would have profound implications for the stability of alpine woody ecosystems.